Placental cord drainage during third stage of labour: a randomized control trial at a tertiary care centre - Chaudhary, Megha; Shah, Maitri; Makwana, Nitin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Labour is a physiological process, but it is often associated with morbidity and mortality, with the most common cause being blood loss. Primary postpartum hemorrhage is commonly defined as a blood loss of 500 ml or more within 24 hours after normal vaginal birth. A prolonged third stage of labour (more than 20 min) is associated with postpartum hemorrhage. The present study was undertaken with the objective of assessing efficacy of placental cord drainage (PCD) during active management of third stage of labour. Methods: This is a randomized control trial in which full term primi gravida who were expected to have normal vaginal delivery, admitted in labour room of a tertiary care centre were evaluated for inclusion in the study. Total 126 participants were enrolled after having normal vaginal delivery. In study group (n = 63), placental cord drainage was used for management of third stage of labour while in control group (n = 63), third stage was managed without PCD. Results: The mean difference in duration of third stage of labour in study and control group was 1.79 minute and the mean difference in blood loss during third stage of labour in both groups was 57.86 ml which was statistically significant. Conclusions: The results of this study show small positive effects from cord drainage in reducing the length of the third stage of labour and in reducing the amount of blood loss when compared with those without cord drainage. The observed changes may be of clinical significance in reducing third stage related complications.